A Study on the Effect of Service Quality of Community Child Center on Family Fuction Factors, Internet Use, and Learning Attitude among Children and Adolescents (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The local children's center is known to provide systematic welfare services for children and teenagers. In the current educational situation where non-face-to-face education is active due to Corona19, the purpose of this study is to find out about family functional factors such as family factors and the potential impact of non-face-to-face education on children and adolescents due to Internet use. The survey was distributed and retrieved from October 6 to January 28, 2020, targeting 210 children and teenagers using local children's centers in Seoul and Gyeonggi Province. A total of 208 questionnaires, excluding 2 questionnaires such as omission of records, were derived and the causal relationship of the study model was to be confirmed by applying the existing SERVQUAL model. Hypothesis verification shows that trust, empathy and type of service quality each had a positive and significant effect on health. Second, trust, empathy, and type of service quality each had a positive and significant impact on self. Family health and self-respect have positively affected learning attitudes, respectively. Based on the results of this study, we believe that it can be used as basic data for the development and policy direction of local children's centers.